COMPARISON OF EPIDURAL CATHETER TIP PLACEMENT BETWEEN MEDIAN AND PARAMEDIAN TECHNIQUES WITH FLUOROSCOPY - Senapathi, Tjokorda Gde Agung; Aribawa, I Gusti Ngurah Mahaalit; Ryalino, Christopher; Leton, Yohanes PT (Bali Journal of Anesthesiology, 2018)
Introduction: The installation of an epidural catheter can be perform by median or paramedian techniques with the aim of position the epidural catheter tip being posterior to the epidural space. The goal of this study was to compare the location and position of the epidural catheter tip placed by the median technique compared to the paramedian technique by using fluoroscopy method.Patients and Methods: Fifty patients aged 18- 65 years who underwent lower abdominal surgery and lower extremities surgery are classified into two groups by consecutive sampling. The first group consists of those who were inserted epidural catheter by median technique approach, and the second group by paramedian technique approach. From the fluoroscopy imaging, the catheter position was classified into one the the following: anterior, posterior, and lateral. Result: In median approach, the epidural catheter tip were placed 16% anteriorly, 20% posteriorly, and 64% laterally. In the paramedian approach, the epidural catheter tip were placed 4% anteriorly and 96% posteriorly. The paramedian approach is more superior to median technique in terms of expected epidural catheter tip position (p <0.001, RR 4.8, CI95%=2.183-10.556). Conclusion: Placement of the catheter tip in the epidural space using paramedian technique is a better option than the median technique.